Effects of temperature on anti-Candida activities of antifungal antibiotics. - Odds, F C (1993)
The relative growth (percentage of growth relative to control growth) of 767 Candida isolates representing five species was measured in microcultures at 25 and 37 degrees C. In the presence of 10(-4) M flucytosine, the distribution of relative yeast growth data indicated that Candida albicans isolates were less susceptible at 25 degrees C than at 37 degrees C, while the opposite was found with 4 x 10(-5) M amorolfine for most of the isolates tested. Repetition of the experiments at four different temperatures with 99 C. albicans isolates and five antifungal agents confirmed a direct relationship between growth inhibition and increasing temperature from 25 to 40 degrees C with amphotericin B, flucytosine, and terconazole; a strong inverse relationship between inhibition and temperature with amorolfine; and a weak inverse relationship with terbinafine. However, these relationships were not always noted with other Candida spp.: in particular, the growth of C. glabrata and C. parapsilosis isolates tended to be greater at 37 degrees C than at 25 degrees C in the presence of the azole-derivative antifungal agents itraconazole and terconazole. These findings stress the species-specific individuality of yeast susceptibility to azole antifungal agents. The results with C. albicans and amorolfine and terbinafine accord with their known in vivo efficacy in mycoses involving low-temperature superficial sites and poor activity against mycoses involving deep body sites. The data also reinforce the need for control of experimental variables such as temperature in the design of standardized yeast susceptibility tests.